Interactions of the p107 and Rb proteins with E2F during the cell proliferation response. - Schwarz, J K (1993)
The E2F transcription factor is found in complexes with a variety of cellular proteins including the retinoblastoma tumor suppressor protein. Various assays have demonstrated a tight correlation between the functional capacity of Rb as a growth suppressor and its ability to bind to E2F. Moreover, only the underphosphorylated form of Rb, which appears to be the active species, interacts with E2F. Despite the fact that the majority of Rb becomes hyperphosphorylated at the end of G1, we now show that the E2F-Rb interaction persists through the G1/S transition and into S phase. A distinct E2F complex does appear to be regulated in relation to the transition from G1 to S phase. We now demonstrate that this complex contains the Rb-related p107 protein. Moreover, like the Rb protein, p107 inhibits E2F-dependent transcription in a co-transfection assay. This result, together with the observation that free, uncomplexed E2F accumulates as cells leave G1 and enter S phase, suggests that the p107 protein may regulate E2F-dependent transcription during G1. In contrast, although Rb does regulate the transcriptional activity of E2F, this association does not coincide with the G1 to S phase transition.